BELAJAR DARI NEGARA TETANGGA; CATATAN WISATA ILMIAH KE SINGAPURA - Kosim, Mohammad (JURNAL KARSA (Terakreditasi No. 80/DIKTI/Kep/2012), 2012)
Mohammad Kosim (Penulis, dosen STAIN Pamekasan, Jl. Raya Panglegur Km. 04 Pamekasan. Kontak person 081330603147, alamat Perumnas Tlanakan Indah Pamekasan) Â  Â  Abstract Singapore is a small country that makes a go of success in developing its region in shorter time. This country consider itself as modern and authoritative country not more than fifty years from its independence procalamation. Singapore has been changed amazingly from the fisherman village into respected country that economically prosperous due to the seriousness of the government in running the country. The success of organizing education takes this country to be one of educational destination countries in the world. The life of religion is well-maintained. Astonighingly, it becomes the cleanest and lowest curruption rate country in the world. Kata-kata kunci Singapura, Indonesia, Islam, pendidikan